La alteridad como concepto clave en la antropología jurídica (2018)
Multiculturalism is a part of Colombian political configuration though history has been written down many times with racial prejudices. As a result of social and political struggles nowadays the acknowledgement of cultural and ethnic diversities through Constitutional Law, opens a clearer way toward legal pluralism in order to diversify conflict resolution beyond the legal possibility of State. At the bottom of indigenous and afrodescendant historical development, in Colombia, there is the play between principle of equality and principle of difference. Democratic State, at the same time that promotes the principle of equality, it must recognize coexistence with law and cultures of other traditions (the principle of difference). Thinking philosophically about difference is something rather new, something peculiar of postmodernism. Swiftly we present here one of the possibilities to think the difference: the philosophy of hebrew humanism by Emmanuel Lévinas.